RIELMA No 17/2024 - MIHĂESCU, Manuela (2025)
RIELMA/ IRSAML is the official journal of the Department of Applied Modern Languages at Babeș-Bolyai University. It is an annual peer-reviewed scientific publication that seeks to provide a challenging forum of debate and build toward major research in the vibrant and intensely interdisciplinary area of applied modern languages. Our primary goal is to make a meaningful contribution to the exciting and as yet pioneering effort of charting a new and dynamic territory and become a leading publication venue for new thinking in the field of translation studies, terminology, interpreting, applied linguistics, cultural mediation, cultural and intercultural studies, applied informatics, subtitling and sign language.